LEGAL BASIS FOR THE ESTABLISHMENT OF FOREIGN BANKS IN THE REPUBLIC OF UZBEKISTAN (Proceedings of International Educators Conference, 2024)
The article examines the legal basis for the establishment of foreign banks and their accredited representative offices, discloses the procedure and conditions for the establishment of foreign banks and accreditation of their representative offices, legislative requirements, analyzes and highlights the distinctive features of the norms of banking legislation of the Republic of Uzbekistan.